Memahami Al-Qur’an dengan Teori Ḥadzf - Hilmy Muhammad (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2009)
This article explains how the ellipsis (ḥadzf) theory performs in Qur’anic translation. It explains the philosophy, theory and manners of ḥadzf, and the formulation of deleting word (maḥdzūf) in the sentence (jumlah). This sort of article puts more attention on studying the verse of 125 Surah al-Naḥl [16]. This study shows that ḥadzf can fill the empty space of Qur’anic translation, and its interpretation. It is open for everybody to give his interpretation. However, it requires several conditions to formulating the deleted word (maḥdzūf). Eventually, this article concludes that study of ḥadzf is important in translating al-Qur’an which can make the renders easier to understand the messages of al-Qur’an.